Analysis of Nutrition Status and Economic Factors Affecting Health Survey in Rogoselo Village - Dini Febianti; Hendri Hermawan Adinugraha (Yayasan Adra Karima Hubbi, 2024)
This study aims to analyze the nutritional conditions of children in the village of Rogoselo, who are suffering from malnutrition, stunting, and wasting. The study investigates the factors that cause these nutritional problems, including economic and social factors. The research methods used are qualitative descriptive approaches, which involve in-depth interviews with the mother-in-law, as well as observations of the environmental conditions of the village. The findings show that economic factors such as low family income, high poverty rates, and economic instability contribute to the difficulty of access to nutritious food. Children from low-income families are more likely to suffer from nutritional problems. In addition, poor parents' knowledge of the importance of balanced nutrition is also a supportive factor. The study also found that interventions that include nutritional education, improved access to nutritious food, as well as health support can play an important role in improving the nutritional conditions of children in Rogoselo Village. These programs can help address nutritional problems and have a positive impact on children's well-being. In conclusion, more comprehensive and sustainable action is needed to improve the quality of life of the children in the village.